Sleep Apnea in Patients Hospitalized With Acute Ischemic Stroke: Underrecognition and Associated Clinical Outcomes - Festic, Nura (J Clin Sleep Med, 2018)
STUDY OBJECTIVES: To evaluate clinical recognition of sleep apnea and related outcomes in patients hospitalized with acute ischemic stroke. METHODS: A retrospective study of all patients hospitalized with acute ischemic stroke from April 2008 to December 2014. The primary predictor and outcome variables were sleep apnea and hospital mortality, respectively. Secondary outcomes were mechanical ventilation, hospital length of stay, and the survivor's functional level by the modified Rankin scale. A sensitivity multivariate regression analysis included the propensity score for cardiovascular comorbidities and sleep apnea. RESULTS: Of 989 patients, 190 (19%) were considered to have sleep apnea. Only 42 patients (22%) received any treatment for sleep apnea during the hospital stay. Despite higher prevalence of cardiovascular comorbidities, the patients with sleep apnea had lower hospital mortality, 1% versus 5.6% in patients without sleep apnea (odds ratio [OR] 0.18; 95% confidence interval [CI], 0.03–0.58, P = .002). Only the National Institutes of Health Stroke Scale (NIHSS) and the Glasgow coma scale (GCS) were significant predictors of adjusted hospital mortality (OR 1.06, 95% CI 1.01–1.11, P = .01 and OR 0.61, 95% CI 0.51–0.69, P ≤ .001, respectively). A composite clinical propensity score for sleep apnea and cardiovascular comorbidities was significantly associated with decreased mortality, independent to either NIHSS (OR 0.11, 95% CI 0.017–0.71; P = .02) or GCS (OR 0.07, 95% CI 0.01–0.52; P = .01). CONCLUSIONS: Prevalence of sleep apnea in our study was low, likely because of clinical underrecognition. Despite having more cardiovascular disease, the patients with acute stroke and sleep apnea had less severe neurological injury and lower unadjusted mortality than those without a history of sleep apnea. CITATION: Festic N, Alejos D, Bansal V, Mooney L, Fredrickson PA, Castillo PR, Festic E. Sleep apnea in patients hospitalized with acute ischemic stroke: underrecognition and associated clinical outcomes. J Clin Sleep Med. 2018;14(1):75–80.